PERSONAL BRANDING LISA MANOBAL SEBAGAI IDOLA KPOP ASAL THAILAND DI TENGAH ISU RASISME - Maheswari, Maura Raehan; Ardianti, Dhini (Ilmu Komunikasi, FISIP Universitas Pasundan, 2025)
Lisa Manobal is a KPOP idol from Buriram, Thailand, who is a member of the biggest female vocal group in the world, BLACKPINK, from South Korea. As a Southeast Asian KPOP idol, Lisa suffers from discriminatory behavior due to the high issue of racism in South Korea, making it quite difficult for non-Korean idols, especially Southeast Asia, to have a long-lasting career. The purpose of this research is to find out how signs, markers, social reality, and personal branding of Lisa Manobal in the midst of the issue of racism, based on the Woody Show x Lisa broadcast uploaded on YouTube in 2021. The purpose of this research is to find out how signs, markers, social reality, and personal branding of Lisa Manobal in the midst of the issue of racism, based on the Woody Show x Lisa broadcast uploaded on YouTube in 2021. This study uses a qualitative method approach, to deepen the research, the researcher also uses Ferdinand de Saussure's semiotic analysis, Peter L. Berger's social reality construction theory, and Peter Montoya's personal branding theory. Researchers used data triangulation techniques to obtain answers from online interviews with informants. The results of the study shows that, the signified and signifier in the Woody Show x Lisa show are in dialogue, Lisa Manobal is branding herself as a global musician while at the same time opening up about her identity as a Thai amid the issue of racism. In reality, the issue of racism that is rooted in the social environment can become a barrier to one's goals, because there is an attitude of discrimination, and is more concerned with race and origin than quality. However, Lisa Manobal was able to maintain her career and personal branding, based on Peter Montoya's eight personal branding concepts as benchmarks, namely specialization, personality, leadership, distinctiveness, visibility, unity, persistence, and goodwill. Lisa Manobal has these eight concepts that allow her to maintain a career amidst this racism.